The Experiences of Ph.D. Dropouts in Geography - Esma Emmioglu Sarikaya; Ayşe Çağlar (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study examines the experiences of four Ph.D. drop-out students in Geography programs in Turkey. Phone interviews were used to collect data. Narrative inquiry was used as a research design. Snowball sampling was used to reach the participants of the study. The study participants were two men and two women who started their Ph.D. programs in different universities in Turkey. The main reason that the participants had started their Ph.D. degrees was for getting academic jobs. The participants reported that they had positive experiences such as learning new skills and expanding knowledge but also negative experiences during their Ph.D. programs. All participants dropped out of their Ph.D. programs while they were writing their dissertations. Participants reported several personal (e.g., lack of skills) and circumstantial (e.g., social responsibilities, commuting) factors as reasons for quitting their Ph.D. programs. For educators, administrators, and policymakers, we recommended that setting higher criteria for Ph.D. students should be considered to attract and accept the best candidates for doctoral programs. During the doctorate, students should be able to select their supervisors or change their supervisors. In addition, doctoral students should be offered opportunities to socialize, share information, and learn from each other and should be encouraged to cooperate.